Simultaneous determination of two galangin metabolites from Alpinia Officinarum Hance in rat plasma by UF LC-MS/MS and its application in pharmacokinetics study - Rangru Liu; Hailong Li; Na Wei; Yinfeng Tan (PeerJ, 2021)
Galangin has multiple pharmacological efficacies, such as anti-cancer, anti-inflammation and anti-oxidation. Galangin can be rapidly converted into glucuronidated metabolites in vivo. This study aimed to establish an UFLC-MS/MS analytical method to simultaneously determine the concentrations of two glucuronidated metabolites of galangin, galangin-3-O-β-D-glucuronic acid (GG-1) and galangin-7-O-β-D-glucuronic acid (GG-2) in rat plasma. After oral administration of galangal extract (0.3 g/kg), blood samples were collected from the orbital sinus, then treated by methanol precipitation and further gradient-eluted with Phenomenex Kinetex 2.6 µm XB-C18 column. The mass spectrometer was manipulated in the negative electrospray ionization (ESI) and selected multiple reaction monitoring (MRM) mode for the analytes. The precursor-to-product ion pairs applied for GG-1, GG-2 and chrysin (as the internal standard, IS) were m/z 445.2→269.0, 445.2→268.9 and 253.0→142.9, respectively. The results showed that the linear ranges for both GG-1 and GG-2 were 2.0–2000.0 ng/mL (r2 > 0.995). The inter- and intra-day precision were 89.3%–109.2%, RSD was less than 15%, and the repeatability was good. The recoveries of both metabolites and IS were over 89%, and matrix effect was within 15%. The validated analytical method was further applied to study the pharmacokinetic profiles of GG-1 and GG-2 in vivo. The pharmacokinetic parameters suggested that Tmax of GG-1 was equivalent to that of GG-2, and MRT0-t, t1/2 of GG-2 were a little higher than those of GG-1. Importantly, AUC0-t and Cmax of GG-2 were almost twice as those of GG-1. In short, the validated UFLCMS/MS analytical method was feasible to simultaneously determine two galangin metabolites GG-1 and GG-2 in rat plasma and further analyze in vivo metabolism of galangin.